Effects of Recommended Fertilizer Application Strategies Based on Yield Goal and Nutrient Requirements on Drip-Irrigated Spring Wheat Yield and Nutrient Uptake - Liyang Cheng; Xiangjie Chang; Junhua Li (Agronomy)
Excessive application of fertilizers in drip-irrigated wheat production can suppress yields, lower nutrient utilization efficiency, and lead to economic and environmental issues such as nitrogen residues in the soil. Based on a recommended fertilizer application (RF) strategy that takes into account target yield and nutrient requirements, this study explores the responses of wheat plant traits, changes in topsoil and subsoil nutrients, fertilizer utilization, and economic benefits under this strategy. From 2022 to 2023, a field experiment was conducted in a typical oasis spring wheat production area at the northern foot of the Tianshan Mountains in Xinjiang. The treatments included no fertilizer control (CK), the farmer’s conventional practice (FP), recommended fertilizer (RF), RF with nitrogen omission (RF-N), phosphorus omission (RF-P), and potassium omission (RF-K). The results showed that compared with FP, the RF reduced 91 kg N ha−1 (30.3%) and 33 kg P2O5 ha−1 (24.8%) in 2022, and 69 kg N ha−1 (23.0%) and 2 kg P2O5 ha−1 (1.5%) in 2023. The effect in 2023 was better; RF also decreased the NO3−1-N residue in the 0–100 cm soil layer by 40.1 kg N ha−1 compared with FP, with no significant difference in wheat grain yield (RF: 5382.9 kg ha−1) or economic benefit (RF: USD 1613.1 ha−1). Furthermore, there were no significant differences between RF and FP in pre-anthesis NP transport or post-anthesis NP accumulation; however, RF significantly increased pre-anthesis potassium transport volume (15.8%) and transport rate (12.5%). RF led to a 16.3% increase in nitrogen utilization efficiency (NUE), while there was no significant difference in phosphorus utilization efficiency (PUE) compared with FP. The fertilizer yield effect for RF was evaluated as N > P > K. Correlation analysis indicated that grain yield was significantly positively correlated with pre-anthesis NPK transport and post-anthesis NP accumulation. It was also positively correlated with organic matter, alkali-hydrolyzed nitrogen, and Olsen-P content in both the topsoil (0–20 cm) and subsoil (20–40 cm), but not with available potassium in the soil. Therefore, conducting soil tests and determining fertilizer recommendations based on the proposed RF method at harvest can reduce fertilizer usage and achieve a balance between the conflicting objectives of environmental protection, increased crop yields, nutrient utilization efficiency, and improved economic benefits in oasis agricultural areas facing excessive fertilizer application.